Analisis Determinan Tingkat Pengangguran Terbuka di Wilayah Sumatera Periode 2015-2024 - Adawiah, Dita Aulia; Yulmardi; Hastuti, Dwi (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study aims to examine the effects of the provincial minimum wage, poverty rate, economic growth, and the Labor Force Participation Rate on the open unemployment rate in the Sumatra region during the 2015–2024 period. The study is motivated by the persistent fluctuations in the open unemployment rate across Sumatra, while previous studies have reported inconsistent findings regarding its determining factors. A quantitative approach was employed using panel data regression analysis based on data from 10 provinces in Sumatra over the period 2015–2024. The results indicate that the Provincial Minimum Wage has a negative and statistically significant effect on the open unemployment rate (β = −1.4774; p = 0.0058). Similarly, economic growth has a negative and significant effect (β = −0.2553; p < 0.001). In contrast, the number of people living in poverty (β = 0.0596; p = 0.4994) and the Labor Force Participation Rate (β = 0.0261; p = 0.7192) exhibit positive but statistically insignificant effects. The estimated model yields an adjusted R² of 0.3553, indicating that 35.53% of the variation in the open unemployment rate is explained by the variables included in the model. These findings suggest that promoting inclusive economic growth and implementing appropriate minimum wage policies may contribute to reducing the open unemployment rate in the Sumatra region.